Translanguaging Pedagogy in ELT Practices: Experiences of Teachers in Indonesian Pesantren-based Schools - Ahmad Madkur; Yuliana Friska; Lisnawati Lisnawati (VELES Voices of English Language Education Society, 2022)
Despite the prevalence of English-only instruction in foreign language classrooms, many affirm the use of diverse linguistic repertoires particularly in linguistically-diverse society contexts where multilingual learners tend to naturally function their linguistic repertoires at daily basis (Canagarajah, 2011). This study aimed to explore teachers’ attitude toward the translanguaging approach in English language teaching (ELT) practices in pesantren schools and how it is used in the learning process. Six-phase thematic analysis was used as its qualitative research method and data were generated via in-depth semi-structured interviews to English teachers in pesantren-based schools in Lampung province. The findings showed that teachers had positive attitude toward translanguaging, as it allows them to take benefits of students’ languages other than English in English classroom. They found translanguaging helpful to explain, elaborate, and reinforce the meaning of learning materials as well as to motivate students and to create enjoyable learning atmosphere. In addition, the accommodation of knowledge or skills of other languages serves as a way to integrate the local and contextual values and culture of pesantren schools into English classroom. Some practical pedagogical implications for are discussed.